Sucata & Diamante: o jogo como metodologia de criação do artista-docente - SOUZA JÚNIOR, Enoque Paulino de (2018)
This searching was made by the play “Sucata & Diamante”. It has as a goal, analyze the process artistic pedagogic created by Dirigível Coletivo de Teatro in the year of 2012 in Belém-Pa. Considering that the methodology used in this creation process was Theather Games, this searching will, analytically describe, the utilization of this methodology inside of the creation of the scenes from a play that has Street Theater as its language. It also shows that this process, which was totally experimental, is the first great challenge to this new group in search of its own theatrical artistic language.